IMPLEMENTATION OF SOCIAL FORESTRY POLICY IN THE WANA MANUNGGAL COMMUNITY FOREST KPH LAKITAN BUKIT COGONG MUSI RAWAS DISTRICT, SOUTH SUMATRA - Heripan, Heripan; Pratama, Angga Septian Muda; Rosianty, Yuli (Universitas Muhammadiyah Palembang, 2023)
This research was carried out to determine the implementation of social forestry. One of the areas that has implemented the social forestry pattern is the forest area in the management area of the Regional Technical Implementation Unit (UPTD) KPH Region XIII Lakitan Bukit Cogong which is located in Musi Rawas Regency.. So the aim of This research aims to determine the process of implementing social forestry policies and determine the influencing factors. The research was conducted at HKM Wana Manunggal, Sukakarya Village, Musi Rawas Regency, using a qualitative descriptive approach method. Based on the data analyzed, financial resources are still lacking and human resources (staff) are sufficient. The collective action process between actors is running well with the presence of a committed PPS Working Group. Communication is going well between the community (forest farmer groups and members of HKM Wana Manunggal) and communication is also very good between the government structure, village heads and officials and the regional government. The social forestry policy at HKM Wana Manunggal KPH Lakitan Bukit Cogong, Musirawas Regency, has been implemented effectively from the perspective of policy accuracy in resolving forestry problems and environmental accuracy in accepting policies.